Systematic Scoping Review of Socioeconomic Burden and Associated Psychosocial Impact in Patients With Rare Kidney Diseases and Their Caregivers - Anna Palagyi; Agnivo Sengupta; Monica Moorthy; Charu Malik; Jonathan Barratt; Olivier Devuyst; Ifeoma I. Ulasi; Daniel P. Gale; Siyuan Wang; Blake Angell; Vivekanand Jha; Stephen Jan (Kidney International Reports)
Introduction: Rare kidney diseases constitute a significant public health challenge but have attracted limited research investment. The evidence about the socioeconomic burden of rare kidney diseases has not been systematically examined. Such evidence is critical for generating the advocacy and awareness necessary to impel scientific and policy investment in targeted care in health systems worldwide. We aimed to evaluate the socioeconomic burden borne by patients with rare kidney diseases, their families, and caregivers, and the related psychosocial impact. Methods: We undertook a systemic scoping review of the recent evidence of the socioeconomic and psychosocial burden of rare kidney diseases, to identify gaps in the understanding of this burden across contexts and factors influencing them. Three databases and the grey literature were searched for relevant studies published in the 10 years before April 30, 2023. Results: Fifty-three articles met the inclusion criteria; one-quarter of these articles included rare disease cohorts in which the kidney was the primary organ affected, and 91% of studies were conducted in high-income countries. Evidence of substantial life-long socioeconomic burden emerged across the following 4 main categories: education (n = 17 articles [32%]), work and employment (n = 40 [75%] articles), psychosocial and emotional impact (n = 17 [32%]), and out-of-pocket expenses (n = 15 [28%]). Conclusion: Significant gaps in our understanding of the socioeconomic burden remain, particularly in lower-resource health systems, among traditionally marginalized populations, and for rare diseases for which kidney is the primary affected organ. Further exploration of socioeconomic burden within these populations is vital to inform effectively targeted investment in advocacy and health care innovation for affected individuals.